PENGARUH DOPING CHROMIUM TERHADAP SIFAT MAGNETIK NANOPARTIKEL OKSIDA BESI - Indah Tamara Sitorus; Erwin Amiruddin; Juandi Muhammad; Erman Taer (Universitas Riau, 2023)
The purpose of this study is to determine the magnetic properties expressed in the hysteresis loop as well as the morphology of iron oxide nanoparticles from iron sand of Logas Village, natural sand, which were doped with chromium. The separation between magnetic and non-magnetic particles was carried out using the strong magnet neodymium iron boron (NdFeB). Magnetic nanoparticle preparation was carried out by ball milling method for 100 hours which is called BM3. The BM3 product was divided into three parts with the same amount of weight namely BM3A, BM3B, and BM3C. These products was doped with chromium with concentrations of 0, 10, and 20 (wt%) using ball milling for 20 hours. Magnetic properties were tested using a vibrating sample magnetometer and nanoparticle morphology with a scanning electron microscope (SEM). The magnetic properties of the samples were studied based on loop hysteresis showed that saturation magnetization, remanent magnetization, coercivity, loop squareness, and loop area decreased along with the addition of chromium doping concentration in the sample. The results of the SEM test showed that as the doping concentration was added to the sample the particle size became smaller, namely 1.316, 1.308, and 0.856 μm.